2018
DOI: 10.1097/mpa.0000000000000966
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Serum Thymidine Kinase Activity as Novel Monitoring, Prognostic, and Predictive Biomarker in Pancreatic Cancer

Abstract: Pancreatic ductal adenocarcinomas reveal a significant increase in S-TK activity, which is associated with overall survival, especially in early tumor stages. Serum thymidine kinase 1 activity may be a useful parameter for monitoring nTx efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Regarding survival, high sTK1 level was an independent prognostic factor for both PFS and OS in patients with newly diagnosed MBC. These results support previous studies reporting impaired survival in patients with high TK1 levels in different malignancies [11][12][13] . When evaluating sTK1 levels during therapy as a tool for monitoring treatment in MBC we found that the median cut-off of initial sTK1 level was relevant for correlation to both PFS and OS at follow-up time points at 3 and 6 months.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding survival, high sTK1 level was an independent prognostic factor for both PFS and OS in patients with newly diagnosed MBC. These results support previous studies reporting impaired survival in patients with high TK1 levels in different malignancies [11][12][13] . When evaluating sTK1 levels during therapy as a tool for monitoring treatment in MBC we found that the median cut-off of initial sTK1 level was relevant for correlation to both PFS and OS at follow-up time points at 3 and 6 months.…”
Section: Discussionsupporting
confidence: 92%
“…60 In humans, preoperative measurements of TK1 activity with the DiviTum assay provide prognostic information in primary breast, lung, and renal cancers. 64,77,78 The DiviTum assay provides valuable clinical information in the treatment and management of chronic lymphocytic leukemia. 62 Consequently, the DiviTum method is valuable to encourage further investigation in veterinary patients.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were run in batches depending on the number of samples and transported in ice pack by express/overnight service. Analysis of TK1 activity was determined by a refined enzyme‐linked immunosorbent assay (ELISA), the DiviTum assay (Biovica International, Uppsala, Sweden), according to the manufacturer's instructions (http://biovica.com/), as previously described . Serum was added to reaction mixture, containing bromodeoxyuridine (BrdU), in a 96‐well ELISA titer plate.…”
Section: Methodsmentioning
confidence: 99%
“…The median TKa was 42 Du/L (range <20-1787 Du/L), while, as a reference, in 123 healthy subjects, the median TKa value was <20 Du/L (Biovica data on file). In a cohort of preoperative pancreatic cancer patients, the median TKa value was 40 Du/L, and in a cohort of preoperative renal cell cancer patients, the median TKa was 38 Du/L [12,14]. Further, in a cohort of non-small cell lung cancer patients, the median TKa was 129 Du/L before the start of systemic treatment, whereas in a cohort of breast cancer patients, the pre-treatment TKa was 57 Du/L in patients with locoregional disease and 101 Du/L in patients with visceral metastasis [15,18].…”
Section: Discussionmentioning
confidence: 97%
“…Further, elevated TK enzyme activity has been measured in blood samples from cancer patients and is associated with tumor proliferation and tumor burden [8]. Circulating levels of TKa, measured with the DiviTum assay, have been shown to be associated with disease stage, prognosis, and treatment efficacy in several cancer types, including breast, lung, pancreatic, and renal cell cancer [9][10][11][12][13][14][15]. This study is the first to analyze TKa levels in the plasma of melanoma patients.…”
Section: Introductionmentioning
confidence: 99%